EXPLORING THE INFLUENCE OF NURSING QUALIFICATIONS AND TENURE ON PATIENT CARE PERCEPTIONS IN SAUDI HEALTHCARE FACILITIES - Talal Khalaf Aqla Aldhafeeri, Abdullah Mutlaq Dakhel Alshammari, Mansour Malahi Al-Harbi, Awatif Saber Kassar Alanazi, Najeeb Mutlaq Dakhel Alshammari, Fahad Mohammed Mofareh Alharbi (Chelonian Research Foundation, 2022)
The nursing workforce plays a vital role in shaping patient care perceptions and overall healthcare quality. Nurses' qualifications and professional experience are considered key factors influencing their performance and patient satisfaction. This study aimed to explore the impact of nursing qualifications and tenure on patient care perceptions in Saudi healthcare facilities. A cross-sectional survey was conducted among 621 nurses and 621 patients from various healthcare settings in Riyadh, Saudi Arabia. Nurses' qualifications and years of experience were assessed using a self-reported questionnaire, while patients' perceptions of care were measured using the Patient Satisfaction Questionnaire Short-Form (PSQ-18). Multiple linear regression analysis revealed that nursing qualifications and tenure were significant predictors of patient care perceptions, with higher qualifications and longer tenure associated with better patient ratings. The findings highlight the importance of investing in nurses' education and professional development to enhance patient care quality and satisfaction in Saudi healthcare facilities. Keywords: nursing qualifications, nursing tenure, patient care perceptions, healthcare quality, Saudi Arabia